Avaliação do uso de gabros e sienitos como potenciais remineralizadores de solos - Santos, Henrique Rodrigues dos (2023)
Brazil has gradually become a more agro-exporting country and is currently consolidating itself as one of the largest food producers in the world. In this context, there is a growing expansion of national agribusiness-related sectors, generating a high demand for fertilizers, given that national soils are deficient in potassium. Other fertilization techniques have been studied to mitigate dependence on external fertilizers, such as rocking. This technique is based on the addition of dust from various types of rocks with the aim of rejuvenating impoverished or lixiviated soils. This study aims to evaluate the potential of gabros and sienitos belonging to the Alcalinas Canamã unit, especially as regards their use as rock powders. In terms of imports, in 2021 alone, domestic agriculture was responsible for 8.5% of world fertilizer consumption, in which about 85% of fertilizers used in the country come from these imports. Thus, using the parameters established by the regulatory instruction n.05/2016 of the MAPA, which regulates the registration of soil remineralizers, only the composite samples (gabros and sienitos combined in the ratio of 1:1) essentially meet all the requirements established in the regulation. In view of this, it was possible to idealize optimized proportions in order to obtain a more complete and efficient soil remineralizer, with 1:4 (gabbro:sienito) the most advisable ratio. However, although these rocks present promising results, especially if we consider factors such as composition, rock volume and area access, there is still a need for multidisciplinary studies, such as those of agronomic efficiency, lixiviation tests, solubilization and incubation, in order to understand their full potential as soil remineralizers.